On new Hermite-Hadamard type inequalities for F-convex functions via fractional integrals - Budak, Hüseyin; Kösem, Pınar; Khan, Sundas (Sarajevo Journal of Mathematics, 2022)
In this article, we investigate two new Hermite-Hadamard type inequalities for F-convex functions via fractional integrals. Some special cases are also discussed as a refinement of previously known results.